POLA KEHIDUPAN BERAGAMA DALAM MASYARAKAT ISLAM - Samsinas Samsinas (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2013)
This paper deals with the forms of religious life among Islamic community in the village of Sidondo, the district of Sigi Biromaru. The approach adopted in this paper is sociological and historical. The result shows that; first, the forms and structures of communication in religious life among society follow the command of Religious Committee in the village. Second, the model of religious understanding which was historically established for a long time is a combination between sufistic-oriented teachings promoted by the first Muslim propagater in Sidondo, which is called Karaeng, and shari'a-oriented teachings taught by Guru Tua, the founder of Alkhairaat, which have been spread by Alkhairaat organization in Sidondo village. Third, forms of religious behavior is not significantly different from Islamic community in general.